Ferritin Heavy-like subunit is involved in the innate immune defense of the red swamp crayfish Procambarus clarkii - Zhang, Si-Pei; Zhang, Jie; Wang, Qing-Hao; Ye, Yang; Zhang, Dai-Zhen; Liu, Qiu-Ning; Tang, Bo-Ping; Dai, Li-Shang (Frontiers in Immunology, 2024)
Iron-binding proteins, known as ferritins, play pivotal roles in immunological response, detoxification, and iron storage. Despite their significance to organisms, little is known about how they affect the immunological system of the red swamp crayfish (Procambarus clarkii). In our previous research, one ferritin subunit was completely discovered as an H-like subunit (PcFeH) from P. clarkii. The full-length cDNA of PcFerH is 1779 bp, including a 5'-UTR (untranslated region, UTR) of 89 bp, 3'-UTR (untranslated region, UTR) of 1180 bp and an ORF (open reading frame, ORF) of 510 bp encoding a polypeptide of 169 amino acids that contains a signal peptide and a Ferritin domain. The deduced PcFerH protein sequence has highly identity with other crayfish. PcFerH protein's estimated tertiary structure is quite comparable to animal structure. The PcFerH is close to Cherax quadricarinatus, according to phylogenetic analysis. All the organs examined showed widespread expression of PcFerH mRNA, with the ovary exhibiting the highest levels of expression.Additionally, in crayfish muscles, intestines, and gills, the mRNA transcript of PcFerH was noticeably up-regulated, after LPS and Poly I:C challenge. The expression of downstream genes in the immunological signaling system was suppressed when the PcFerH gene was knocked down. All of these findings suggested that PcFerH played a vital role in regulating the expression of downstream effectors in the immunological signaling pathway of crayfish.